2002
DOI: 10.1161/01.hyp.0000030198.48441.65
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Study of Endothelial Function in White Coat Hypertension

Abstract: Abstract-Several studies have demonstrated that endothelial dysfunction is present in patients with essential hypertension.However, the presence of endothelial dysfunction in patients with white coat hypertension has not been studied. We evaluated the variation in the diameter of the brachial artery produced by flow-mediated dilation after a mechanical stimulus in patients with recently diagnosed mild to moderate sustained essential hypertension compared with patients with white coat hypertension. A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 51 publications
2
20
1
1
Order By: Relevance
“…These data collectively indicate that FMD does not appear to be impaired by an acute increase in SNA. The data are consistent with the no impairment of FMD in one study of white-coat hypertension (29), but this finding is controversial (13,22) and awaits further explanation of the link to the consistent finding of impaired endothelial function with essential hypertension (10,26,28). There are important implications from the current study.…”
Section: Sympathetic Activation and Stress Responsesupporting
confidence: 86%
See 1 more Smart Citation
“…These data collectively indicate that FMD does not appear to be impaired by an acute increase in SNA. The data are consistent with the no impairment of FMD in one study of white-coat hypertension (29), but this finding is controversial (13,22) and awaits further explanation of the link to the consistent finding of impaired endothelial function with essential hypertension (10,26,28). There are important implications from the current study.…”
Section: Sympathetic Activation and Stress Responsesupporting
confidence: 86%
“…Lind et al (24) noted that, although the magnitude of FMD with acute mental stress was not different from control, the ratio of FMD to blood flow was significantly reduced. Many of the studies (9,13,14,17,29,35) cited here either did not measure blood flow during hyperemia or did not report the data. To achieve the same peak shear stress in our mental arithmetic test as in the control, we reduced the duration of the period of occlusion.…”
Section: Sympathetic Activation and Stress Responsementioning
confidence: 99%
“…In the PAMELA study, Cardillo, Weber, Mancia and Mulè reported that LVMI was increased in WCHT patients compared with NT patients (P < 0.01), whereas Pierdomenico and Hoeghelm found no difference in LVMI [5,[26][27][28][29][30][31] . Arterial compliance was lower in WCHT patients than in the NT group in studies by Karter's (P < 0.001) and Gomez [25,32] . Turfaner et al [33] analyzed 47 dipper and 43 non-dipper WCHT patients and determined, that non-dipping in WCHT patients was related to decreased arterial compliance and that the global risk load for target organ damage was higher in non-dipper WCHT subjects.…”
Section: Prognosis and Stroke Risk In Patients With White-coat Hypertmentioning
confidence: 83%
“…Although adult studies find that patients with WCH have lower LVM than those with sustained hypertension, their cardiac mass is higher than that of normal controls. 43 Furthermore, other forms of target organ damage, such as endothelial dysfunction 44 and increased c-IMT, 45 are associated with WCH and may account for the increase in adverse cardiovascular disease outcomes noted with this condition. 46 Data in children are sparse, but youth with WCH have been shown to have greater body mass index and a tendency toward elevated LVM index, strengthening the indications for ABPM follow-up of WCH.…”
Section: White Coat Hypertensionmentioning
confidence: 99%